Evaluation of orofacial pain and psychological comorbidities in health sciences university students - Fong Lim Xin; Veerabhadrappa Suresh Kandagal; Yadav Seema; Bin Zamzuri Ahmad Termizi; Talib Rozaidah Binti (EDP Sciences, 2021)
Introduction: Orofacial pain (OP) is a common public health problem among the general population however, its distribution among the young population like students has not been evaluated so far. The objectives of this study were to investigate the self-reported prevalence, and characteristics of OP, and to evaluate its association with psychological comorbidities such as anxiety and depression. Materials and Methods: A questionnaire-based study was conducted on students studying health sciences programs at SEGi University, Malaysia. A well-designed, structured questionnaire was utilized to assess the prevalence and characteristics of OP. Hospital Anxiety and Depression (HAD) scale was used to evaluate the psychological status of the students. The collected data was subject to statistical analysis by using the SPSS version 22 software. Results: Overall 494 university students had participated in the study of which, 78% (n = 375) of students had suffered from OP and it was significantly higher among the female students (p < 0.03). Headache was the most common type of OP (66.2%) followed by pain in temple region (47.2%), in and around eyes (29.1%), facial region (23.3%), and tooth/gingival pain (20.9%). The association between the prevalence of OP and anxiety was statistically significant (p < 0.019). About 35.4% of the health sciences students had first OP episode started three months ago, 4.2% had daily pain, 14.3% suffered from continuous pain, and only 14% of the students had consulted professionals and 36.1% of them took medication. Conclusion: A significantly higher prevalence of self-reported OP was evident among the health sciences university students and students with different types of OP had higher anxiety and depression scores. Early recognition of OP symptoms and associated comorbidities must be considered for the prevention and successful management of these conditions to circumvent its negative academic impact on the students.